Asthma phenotypes identified by latent class analysis in the ISAAC phase II Spain study. Issue 2 (18th January 2013) - Weinmayr, G.; Keller, F.; Kleiner, A.; du Prel, J. B.; Garcia‐Marcos, L.; Batllés‐Garrido, J.; Garcia‐Hernandez, G.; Suarez‐Varela, M. M.; Strachan, D. P.; Nagel, G.
Summary Background Classification of respiratory symptoms may help to identify different underlying asthma phenotypes reflecting differences in aetiology and prognosis of wheezing disease among children. Objective To determine childhood asthma phenotypes based on respiratory symptoms from a widely used questionnaire to further classify phenotypes in international settings. Methods Between 2000 and 2002 cross‐sectional studies were performed in four centres in Spain. Parental questionnaires were used to collect information on allergic diseases in more than 4000 children aged 8–12 years. In addition, objective markers for allergic sensitization and bronchial hyperresponsiveness (BHR) were measured. Latent class analyses (LCA) were applied to identify subgroups of children according to respiratory symptoms, and then the association of these groups with relevant clinical features such as concomitant allergic disease symptoms, atopy and BHR was studied. Results We found seven classes, one corresponding to healthy children, three classes related to wheeze and three other classes mainly related to congestion and coughed‐up phlegm. These tentative phenotypes differed in severity of symptoms and also in clinical correlates such as BHR and allergic sensitization. Atopy was more predominant in the 'wheeze phenotypes' whereas concomitant 'allergic' symptoms were most frequent in two of the 'wheeze phenotypes' and one of the 'cough phenotypes'. Conclusions LCA on reported symptoms in a cross‐sectional survey allowed different subgroups with meaningful clinical correlates to be defined. It remains to be investigated to what extent these groups also have different aetiologies, prognoses and therapeutic needs.